Universities’ Role in Curriculum Reform: Ecological Public Health Education for Sustainable Health Development - Alice M. L. Li (Current Innovations in Disease and Health Research Vol. 7, 2023)
In claiming that the foresight of the latest transition in this 21st Century has now emerged, as the eco-environmental and climate mediated health risks have increasingly become a priority for sustainable health implications. This chapter specifically urges universities to take the lead in curriculum reform by incorporating these epistemology competencies through transformative health education agenda. In order to support sustainable health developments in transition across intergenerations, it is pivotal for universities acting proactively as capacity building blocks for training all healthcare professionals with the necessary essentialities for a transformative health education agenda. According to Omran’s three key stages of epidemiologic transition as in the Age of (i) Pestilence and hunger, (ii) Preceding Pandemics, (iii) Degenerative and Man-Made Diseases, plus with the later fourth stage of (iv) Delayed Degenerative Diseases as postulated by Olshansky and Ault, all of which shows progressive shifts in disease patterns described as in these typical and successive stages are by no means easy. Especially nowadays under these large-scale changes of global environmental degradation and climate crisis in the Anthropocene that in fact is predominantly affecting global public health. Henceforth, Li has postulated the latest or successively the fifth stage of epidemiologic transition should be in the Age of Environmental and Climate Mediated Health Risks. For this reason, the current 'Bio-medical' model of disease-oriented only emphasizes from the past four epidemiological stages appears to be insufficient under these existential unprecedented phenomena with actual and potential catastrophic and highly complex dynamics of direct and indirect effects on widely diverse health impacts in this new epoch. Planetary health is now scientifically supported as the ultimate ecological determinant that influences sustainable development in health, thus the establishment of health education on ecological public health is crucial to the global public health in transition under this new epoch of the Anthropocene.